Pengaruh Kepemilikan Institusional, Profitabilitas, Corporate Governance, Dan Ukuran Perusahaan Terhadap Pengungkapan Corporate Social Responsibility - Silvia Wulandari; Rina Trisnawati (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to examine the influence of institutional ownership, profitability, corporate governance, and company size on corporate social responsibility (CSR) disclosure in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2018-2022. The population of this study consists of all manufacturing sector companies listed on the IDX during the period 2018-2022, totaling 185 companies. This study utilizes secondary data obtained from the annual reports of companies listed on the IDX from 2018 to 2022. The sampling technique employed is purposive sampling, resulting in a sample size of 36 companies. The sample comprises 151 company data from the years 2019 to 2022. Data collection is conducted using the documentation method with multiple linear regression analysis. The results indicate that institutional ownership, company size, and corporate governance do not significantly influence CSR, whereas profitability significantly affects CSR.